2008
DOI: 10.1111/j.1526-4610.2007.01029.x
|View full text |Cite
|
Sign up to set email alerts
|

Trigeminal Neuralgia as the Sole Manifestation of an Arnold‐Chiari Type I Malformation: Case Report

Abstract: Arnold-Chiari type I malformations usually manifest clinically with short-lasting headaches typically involving the occipital-nuchal region and precipitated by the Valsalva maneuver, coughing, sudden postural change, or physical exertion. We describe the case of an adult patient who presented with symptomatic trigeminal neuralgia caused by an Arnold-Chiari type I malformation. Unlike previous cases, the malformation involved the trigeminal ophthalmic division alone.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
7
0

Year Published

2008
2008
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 13 publications
(7 citation statements)
references
References 10 publications
0
7
0
Order By: Relevance
“…The spinal nucleus, the first relay of trigeminal fibres sensitive for pain in the spinal trigeminal pathway, extends from pontomedullary junction to C2 segment of the spinal cord, and compression of this pathway by cerebellar tonsillar herniation as well as cervical spinal syrinx could cause TN 4. Improvement in symptoms upon decompression of posterior fossa lends further support to this hypothesis 2 4. Third, it has been proposed that the presence of a cervical syrinx may contribute to TN symptoms.…”
Section: Discussionmentioning
confidence: 96%
“…The spinal nucleus, the first relay of trigeminal fibres sensitive for pain in the spinal trigeminal pathway, extends from pontomedullary junction to C2 segment of the spinal cord, and compression of this pathway by cerebellar tonsillar herniation as well as cervical spinal syrinx could cause TN 4. Improvement in symptoms upon decompression of posterior fossa lends further support to this hypothesis 2 4. Third, it has been proposed that the presence of a cervical syrinx may contribute to TN symptoms.…”
Section: Discussionmentioning
confidence: 96%
“…1,3,11,[13][14][15][16][17] It has been more commonly linked to syringobulbia associated with a variety of hindbrain malformations. 8 As demonstrated in the imaging in this particular patient, there was no evidence of syringobulbia or hydrocephalus to explain the symptoms of facial pain.…”
Section: Discussionmentioning
confidence: 99%
“…Rosetti et al 13 suggested that involvement of the nucleus of the spinal trigeminal tract and the principal sensory nucleus of the trigeminal nerve with segmental demyelination of the trigeminal nerve fibres may be responsible for the development of trigeminal neuralgia. Caranci et al 14 reported that chronic extrinsic compression on the trigeminal pain pathway by herniated cerebellar tonsils was the neuropathological basis of facial pain in patients with Arnold-Chiari type I malformation. A distinctive feature of the tumour in the present case was the firm attachment to the brainstem, where the nucleus of the spinal trigeminal tract and the principal sensory nucleus of the trigeminal nerve are located.…”
Section: Discussionmentioning
confidence: 99%